Unusual brain images of a boy with adolescent cerebral X-linked adrenoleukodystrophy presenting with exhibitionism: A CARE-compliant case report. Issue 51 (December 2017) - Zheng, Feixia; Lin, Zhongdong; Ye, Xiuyun; Shi, Xulai
Abstract: Rationale: The respective involvements of both the thalamus and exhibitionism in cerebral X-linked adrenoleukodystrophy (X-ALD) have not been reported. Patient concerns: An 11-year-old boy initially presented with exhibitionism and progressive neurobehavioral symptoms. He subsequently developed transient urinary and fecal incontinence, and an unwillingness to eat or communicate. Diagnoses: We conducted contrast-enhanced brain magnetic resonance imaging (MRI), which revealed symmetrical altered signal intensities in bilateral frontal white matter, the basal ganglia, and dorsal thalami, as well as a peripheral rim of contrast enhancement. Diagnosis of adolescent cerebral X-ALD was confirmed on the basis of next generation genetic sequencing analysis. Interventions: We initiated the patient on hormonal replacement therapy. Outcomes: We observed rapidly progressive neurologic deterioration in this patient, and the boy fell into a vegetative state 10 months after discharge. Lessons: We recommend that physicians should not disregard X-ALD in patients with isolated psychiatric symptoms, including hypersexual behavior. The combination of detailed clinical evaluation, MRI, and next generation genetic sequencing can expedite the diagnostic process of atypical variant of X-ALD.